A Just Destination? Exploring Local Hopes, Fears, and Power Asymmetries in East Greenlandic (Tunu) Tourism Development - Markussen, Ulunnguaq; Ren, Carina (Études Inuit Studies, 2023)
This paper examines current actions towards tourism development in East Greenland (Tunu) and the expectations and concerns of locals in Tasiilaq, specifically regarding the possible inclusion of the East Greenlandic hunting culture on the UNESCO World Heritage List. We explore how locals see the potential and impact of the UNESCO recognition on tourism development in the region and its potential effects on local economy, culture, and traditions. Also discussed are the structural challenges faced by the local community as well as their aspirations for sustainable tourism development, unraveling the perception of power asymmetries and injustices between locals and outsiders and between East and West Greenland. The complex and often paradoxical relationship between heritage, cultural identity, and economic growth in tourism is highlighted, pointing to how general challenges and barriers in Greenlandic tourism development are further amplified and distorted in East Greenland. This suggests a need for greater tourism justice in developing all and not just parts of Greenland as a destination. Cet article examine les activités de développement touristique actuel au Groenland oriental (Tunu), en se penchant sur les attentes et les préoccupations des habitants de Tasiilaq, et plus particulièrement sur l’inscription potentielle de la culture de la chasse du Groenland oriental sur la liste du patrimoine mondial de l’UNESCO. Cette étude explore la façon dont les habitants perçoivent le potentiel et l’impact de la reconnaissance éventuelle de l’UNESCO sur le développement du tourisme dans la région et ses effets potentiels sur l’économie, la culture et les traditions locales. Elle aborde également les défis structurels auxquels la communauté locale est confrontée, ainsi que ses aspirations en matière de développement touristique durable, en démêlant la perception des asymétries de pouvoir et des injustices entre les locaux et les étrangers, et entre l’Est et l’Ouest du Groenland. L’article met en évidence la relation ...